Prenatal care of usual-risk pregnant women: potentialities and weaknesses - Andressa Arraes Silva; Mara Julyete Arraes Jardim; Claudia Teresa Frias Rios; Lena Maria Barros Fonseca; Liberata Campos Coimbra (Universidade Federal de Santa Maria, 2019)
Objective: to know the potentialities and weaknesses in the prenatal consultation of habitual risk. Methods: qualitative study, developed with twenty pregnant women who underwent prenatal care at Primary Health Care in the city of São Luís in 2017. Data analysis used the Thematic Analysis based on the parameters recommended by the Ministry of Health. Results: the reception, the easy access, the examinations and the groups of pregnant women are configured as prenatal potentialities. The lack of organization of the units, of essential drugs, of material resources, the long time to start consultations and the accomplishment of the examinations constituted weaknesses. Conclusions: the assessment of prenatal care from the users' perceptions brought contributions to interventions in the weaknesses of health services to pregnant women, according to the recommendations of the Ministry of Health.